MEMPERTAHANKAN “SOCIAL WISDOM” DI LINGKUNGAN RAUDHATUL ATHFAL TAUFIQURRAHMAN, DEPOK - Kartika Nuringsih; Harry Kristanto (Jurnal Serina Abdimas, 2025)
Pro-social behavior is a person's intention to provide benefits to others. This intention is considered important for the well-being of social groups at various scales, including school communities. Indonesia has been ranked in the top 10 of the highest achievement index for 6 years, and for the last 3 years has even been named the country with the highest generosity in the world. The growth of sharing intentions can provide benefits to others such as helping, sharing, donating, cooperating, and volunteering. Pro-social behavior helps motivate students to learn and contribute broadly to the classroom and school community. Generosity is a good character trait, so in order to support maintaining social wisdom in the school environment, the activity was conducted again by emphasizing the importance of sharing with friends who are in need of social support. The activity was carried out at Raudhatul Athfal Taufiqurrahman at Beji Timur, Depok, attended by 25 students and accompanying teachers. At the event, students were reminded of the benefits of sharing and giving gifts to friends around the school. In this practice, the children willingly and happily gave the gifts. Support from various parties as a representation of subjective norms so that they become interested in similar activities. The continuity of support from internal and external environments will form intentions and eventually become social care behavior in children. ABSTRAK Perilaku pro-sosial merupakan niat seseorang untuk memberikan manfaat kepada orang lain. Niat ini dinilai penting untuk kesejahteraan kelompok sosial dalam berbagai skala, termasuk komunitas sekolah. Indonesia menduduki peringkat 10 besar indeks pencapaian tertinggi selama 6 tahun, bahkan selama 3 tahun terakhir mendapatkan predikat sebagai negara dengan kedermawanan tertinggi di dunia. Tumbuhnya niat berbagi dapat memberikan manfaat kepada orang lain seperti menolong, berbagi, menyumbang, bekerja sama, dan menjadi sukarelawan. Perilaku pro-sosial membantu memotivasi siswa untuk belajar dan berkontribusi secara luas terhadap kelas dan komunitas sekolah. Kedermawanan merupakan karakter baik sehingga dalam rangka mendukung mempertahankan kearifan sosial di lingkungan sekolah dilakukan kembali dengan menekankan pada pentingnya berbagi kepada teman-teman yang sedang memerlukan dukungan sosial. Kegiatan dilakukan di Raudhatul Athfal Taufiqurrahman di Beji Timur, Depok diikuti 25 siswa bersama guru pendamping. Pada event tersebut siswa diingatkan manfaat berbagi serta memberikan bingkisan kepada teman-teman sekitar sekolah. Dalam praktik ini, anak-anak dengan ikhlas dan suasana gembira memberikan bingkisan tersebut. Dukungan berbagai pihak sebagai representasi norma subjektif sehingga menjadi tertarik dengan kegiatan sejenis. Kontinuitas dukungan dari lingkungan internal maupun eksternal akan membentuk intensi dan akhirnya menjadi perilaku peduli sosial pada anak-anak